The Effect of Circuit Training Exercise on The Physical Conditions of Football Athletes Universitas Muhammadiyah Gorontalo - Giofandi Samin; Gilang Ramadan (JUARA : Jurnal Olahraga, 2023)
This study aims to find out information about the effect of circuit training on physical condition. This research is a pre-experimental study conducted using a one group pre test-post test design. Experimental research is a way to look for a causal relationship (causal relationship) between two factors that are intentionally caused by researchers by reducing other disturbing factors. The number of samples is 17 people obtained from the total sampling technique. The study was conducted for 6 weeks, with 3 meetings each week. The instrument used to measure physical condition was the VO2Max test (Bleep test). The results of data analysis using the t test showed a significant increase in the ability of physical conditions due to the influence of circuit training exercises with (t-count 18.59 > t-table 1.74). Based on the data analysis, it is known that t-count> t-table, it can be concluded that circuit training exercises affect the ability of physical conditions.